1962
DOI: 10.1111/j.1476-5381.1962.tb01447.x
|View full text |Cite
|
Sign up to set email alerts
|

An Action of 5‐hydroxytryptamine on Adrenaline Receptors

Abstract: Contractions of isolated strips of cat spleen due to 5-hydroxytryptamine, adrenaline, histamine and acetylcholine were antagonized by phenoxybenzamine. Responses to both 5-hydroxytryptamine and adrenaline were not blocked in strips which were protected by a high concentration of either 5-hydroxytryptamine or adrenaline throughout exposure to phenoxybenzamine. The contraction due to a large dose of 5-hydroxytryptamine lasted less than 1 hr even when the drug was still present. Strips thus desensitized to 5-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

1965
1965
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 13 publications
2
32
0
Order By: Relevance
“…All washes (indicated by W in the protocol) were by exchange of bath contents for fresh Krebs solution. Benextramine tetrahydrochloride (BHC) was included in order to avoid possible confounding of 5-HT responses due to direct or indirect a-adrenoreceptor stimulation by the agonist (Innes, 1962;Fozard & Mwaluko, 1976;Apperley et al, 1976;Marin et al, 1981). The sighting dose of 10 mM 5-HT was used only to establish tissue viability.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…All washes (indicated by W in the protocol) were by exchange of bath contents for fresh Krebs solution. Benextramine tetrahydrochloride (BHC) was included in order to avoid possible confounding of 5-HT responses due to direct or indirect a-adrenoreceptor stimulation by the agonist (Innes, 1962;Fozard & Mwaluko, 1976;Apperley et al, 1976;Marin et al, 1981). The sighting dose of 10 mM 5-HT was used only to establish tissue viability.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…All washes (indicated by W in the protocol) were by exchange of bath contents for fresh Krebs solution. Benextramine tetrahydrochloride (BHC) was included in order to avoid possible confounding of 5-HT responses due to direct or indirect a-adrenoreceptor stimulation by the agonist (Innes, 1962;Fozard & Mwaluko, 1976;Apperley et al, 1976;Marin et al, 1981). The sighting dose of 10 ,uM 5-HT was used only to establish tissue viability.…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…The production of behavioural and electrocortical sleep by amines with substituted phenyl or indolyl ring structures suggested that they acted through similar mechanisms. Receptors common to adrenaline and 5-hydroxytryptamine occur in a number of systems (Innes, 1962).…”
Section: Adultfowlmentioning
confidence: 99%